2019 8th International Conference on Modeling Simulation and Applied Optimization (ICMSAO) 2019
DOI: 10.1109/icmsao.2019.8880398
|View full text |Cite
|
Sign up to set email alerts
|

Sorting permutations with a transposition tree

Abstract: The set of all permutations with n symbols is a symmetric group denoted by Sn. A transposition tree, T , is a spanning tree over its n vertices VT =1, 2, 3, . . . n where the vertices are the positions of a permutation π and π is in Sn. T is the operation and the edge set ET denotes the corresponding generator set. The goal is to sort a given permutation π with T . The number of generators of ET that suffices to sort any π ∈ Sn constitutes an upper bound. It is an upper bound, on the diameter of the correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…permutations. Subsequently, various polynomial time approximation algorithms were designed [23][24][25]29,30]. Chitturi introduced algorithm D in [24] which finds the upper bound δ in polynomial time, which is the tightest known upper bound when the upper bounds of all trees are summed together.…”
Section: Analysis Of Algorithm D* On Millipede Treementioning
confidence: 99%
See 2 more Smart Citations
“…permutations. Subsequently, various polynomial time approximation algorithms were designed [23][24][25]29,30]. Chitturi introduced algorithm D in [24] which finds the upper bound δ in polynomial time, which is the tightest known upper bound when the upper bounds of all trees are summed together.…”
Section: Analysis Of Algorithm D* On Millipede Treementioning
confidence: 99%
“…Chitturi introduced algorithm D in [24] which finds the upper bound δ in polynomial time, which is the tightest known upper bound when the upper bounds of all trees are summed together. Subsequently, algorithm D * which identifies corresponding the upper bound δ * was designed in [29]. It was shown that δ * is tighter for balanced-starburst tree [29].…”
Section: Analysis Of Algorithm D* On Millipede Treementioning
confidence: 99%
See 1 more Smart Citation
“…Sequential token swapping has been studied before by many researchers in many disparate fields, from discrete mathematics [8,34,37,33,38,29] and theoretical computer science [25,28,19,40,42,3,32,7,26,41,11,10,6] to more applied fields including network engineering as mentioned earlier [1], robot motion planning [14,36], and game theory [22]. On general graphs, the problem is known to be NP-complete [3], furthermore APX-hard [32], and even W [1]-hard with respect to number of swaps [7].…”
Section: Related Workmentioning
confidence: 99%
“…They gave an algorithm for finding short (but not necessarily shortest) paths in the resulting Cayley graphs, and characterized the diameter of the Cayley graph (and thus found optimal paths in the worst case over possible start/destination pairs of vertices) when the tree is a star. Follow-up work along this line attains tighter upper bounds on the diameter of the Cayley graph in this situation when the graph is a tree [37,19,29,11] and develops exponential algorithms to compute the exact diameter of the Cayley graph of a transposition tree [10], though the complexity of the latter problem remains open. Here we show NP-hardness of the slightly more general problem of computing the shortest-path distance between two given nodes in the Cayley graph of a transposition tree (sequential token swapping on a tree), a problem implicit in [1] and explicitly posed as an open problem in [40].…”
Section: Introductionmentioning
confidence: 99%